Environmental consequences of oil and gas extraction on the example of the Bytkiv-Babchenskyi Oil and Gas Field - O. Mandryk; M. Orfanova; Yu. Hrybinyk; M. Stakh; V. Zaritskyi (Екологічна безпека та збалансоване ресурсокористування)
Most technological processes create an anthropogenic burden on the environment, and the oil and gas industry is no exception. Due to oil and gas production in the Bytkiv-Babchenskyi Field area, there is gas pollution in the territory of Pasichna and Bytkiv settlements, oil leaks to the surface, however, it is necessary to strive to minimise the negative impact and preserve the environment. The purpose of the study was to conduct a comprehensive analysis of the ecological state of the atmosphere, soils, hydrosphere and technogenic physical fields (radiation, noise, vibration, electromagnetic) near various oil and gas production facilities of the Bytkiv-Babchenskyi Field to determine the man-made impact of the oil and gas production process. The following methods were used: observation, measurement of environmental indicators, meteorological and physical field parameters, and laboratory analysis methods. A wide range of modern instruments was used, which allows for rapid analysis and determination of physical field parameters. In the laboratory, a more detailed analysis of water and soil samples was carried out using physico-chemical methods of analysis. The determined chemical, physico-chemical indicators of water quality, the content of volatile organic compounds and polyaromatic hydrocarbons complied with the regulatory standards. Among the toxic elements, strontium was detected, the content of which did not exceed the maximum permissible concentration. In terms of salt content, the hydrocarbonate water is slightly mineralised. The soils are low-saline with a neutral pH of the soil solution. The content of mobile iron, phosphorus, and nitrogen compounds is very low, low, and medium, respectively, and organic matter is very high. It was established that the parameters of anthropogenic physical fields do not exceed the permissible standards. The results of the study showed that the technogenic impact of the oil and gas production process on the air, water bodies and soils is within the permissible limits. The practical significance of the results obtained is the comprehensive monitoring of the state of natural objects throughout the year, which is important for oil and gas industry professionals when assessing the environmental impact of oil and gas production facilities and developing environmental protection measures